Democratic leadership style of the madrasah head in resolving conflict at MIN 2 West Lampung - Junaidah; Reni Setiawati; Diana, Nirva; Fauzan, Ahmad; Thahir, Andi; Mas Ayu, Sovia (STIES ALIFA, 2022)
Education is one thing that is very important for humans, as long as humans are still alive in the life of this world then education can never be sparated from him. In the pre-research, researchers obtained an overview of theleadership style of the madrasah head using a democratic leadership style. As for the interview, the researcher is attached in appendix 1. In democratic leadership describes leaders who tend to involve subordinates in making decisions, delegating authority, encouraging participation and deciding work methods and goals. In a democratic leadership style that involves subordinates and has many advantages, however, in democratic leadership at MIN 2 West Lampung, conflicts still occur. Conflict is conflict is the process of directing discrepancies between two or more members or organizational groups that arise because they have different statuses, goals, values or perceptions. The type of research used in this paper is descriptive research, using a qualitative approach. Based on the discussion and analysis of the data in this study, related to the leadership style of the madrasah head in resolving conflicts at MIN 2 West Lampung, it is concluded that. The type of research used in this paper is descriptive research, using a qualitative approach. The way leaders delegate responsibility to subordinates in resolving conflicts is good. The active communication of leaders to subordinates in resolving conflicts is good. The method of decision-making by the head of the madrasah by involving subordinates in resoving conflicts is good. Empatthy that leaders do to their subordinatos in resolving conflictis good.